Conceptual Framework of Mobile Marketing:Spamming the Consumer around the World - Sivarethina Mohan, R.; Aranganathan, P. (Indian Journal of Marketing, 2011)
Mobiles offer brands a way to create a dialogue of interaction with their consumer that is personal, relevant and targeted, and the results of mobile campaigns are more tangible and measurable than those from other mediums. The need for mobile marketing increased due to the increase in the use of mobile phones in our country. As a result, many Fast Moving Consumer Goods companies, banks, magazines and TV stations in the country are carrying out their sales promotions through the mobile phone platform. Mobile marketing is not only cost-effective, but advertisers can be sure their advertisement has been seen by the consumer, which is not the case with TV or print. Mobile Internet is considered as one of the important value added services by the mobile service providers as it has paved the way for mobile marketing in the country. In this article, the author had discussed about the implications, current trends and various dimensions of mobile marketing in India.